FAKTOR INTERNAL DAN FAKTOR EKSTERNAL YANG BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN PRODUK AKKAR JUICE BAR YOGYAKARTA - Gendis Dyah Pitaloka; Nanik Dara Senjawati; Indah Widowati (Agrisociabus, 2022)
The development of the juice bar business has made new business actors appear. With the emergence of new competitors, juice bar entrepreneurs  are forced to pay close attention to consumer behavior and the factors that influence consumers' decisions in buying a product. The research conducted at Akkar Juice Bar aims to analyze the influence of internal factors (lifestyle, motivation, perception, attitude) and external factors (social class and reference group) on consumer decisions in purchasing Akkar Juice Bar Yogyakarta products. The research uses descriptive quantitative research methods with a case study approach. The sampling method for determining respondents used a nonprobability sampling method with an accidental sampling technique as many as 100 respondents. The study used primary data and secondary data. Data collection techniques are carried out using interviews, questionnaires, and documentation. Data analysis techniques with descriptive analysis and logistic regression analysis. The results showed that the factors influenced consumer decisions in purchasing Akkar juice bar products were internal factors namely attitudes and external factors namely the reference group. Keywords: Akkar juice bar, external factors, internal factors, purchasing decision